Thiophene-phenylquinazoline probe for selective ratiometric fluorescence and visual detection of Fe(iii) and turn-off fluorescence for I− and its applications. Issue 12 (20th November 2020) - Harsha, Kannikanti Gavash; Ananda Rao, Boddu; Baggi, Tulsidas R.; Prabhakar, S.; Jayathirtha Rao, V.
Abstract : A 2, 5-bis(4-phenylquinazolin-2-yl)thiophene (BQT) probe is designed, synthesized and explored for selective ratiometric fluorescence and visual detection of Fe 3+ and as a turn-off fluorescence probe for I − anion. Abstract : A 2, 5-bis(4-phenylquinazolin-2-yl)thiophene (BQT) probe is designed, synthesized and explored for selective ratiometric fluorescence and visual detection of Fe 3+ and as a turn-off fluorescence probe for I − anion. BQT is colorless and has blue emission in CH3 CN solution. BQT selectively complexes with Fe 3+, turns its solution from colorless to greenish yellow and enables the ratiometric sensing of Fe 3+ with limit of detection (LOD) and limit of quantitation (LOQ) of 2 × 10 −8 M and 6.1 × 10 −8 M, respectively. Binding constant of BQT with Fe 3+ is found to be 4.1 × 10 −4 M −1 . BQT is also able to sense I − anion present in aqueous solution by selectively turning colorless to yellow and fluorescence quenching with a LOD of 1.7 × 10 −7  M and LOQ of 5.2 × 10 −7 M. BQT sensing ability is not influenced by the presence of other metal ions and anions in the vicinity. The BQT–Fe 3+ complex is thoroughly characterized using MALDI-TOF, NMR and Job's plot. A reversibility experiment with EDTA suggests BQT is a reversible fluorescent chemosensor for Fe 3+ ions. The spectroscopic data of BQT and its complexes are employed to construct a field test kit for qualitative analysis and INHIBIT logic gate.